2009 IEEE International Conference on Systems, Man and Cybernetics 2009
DOI: 10.1109/icsmc.2009.5346110
|View full text |Cite
|
Sign up to set email alerts
|

A multi-objective decision making on reliability growth planning for in-service systems

Abstract: New designs prioritized for the fast time-to-market usually can not carry out sufficient in-house reliability growth testing due to the stringent delivery deadline. Reliability improvement for those systems can be achieved by implementing corrective actions (CAs) on in-service systems. In this paper, three types of effectiveness functions are proposed to measure the reduction rate of failure modes given different CA resources. Integrated with the effectiveness function, a new failure intensity model is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This paper aims to extend the preliminary findings [22] to a multiphase reliability growth environment. The study is motivated to address the stochastic behavior of latent failures and further mitigate their impact on product reliability.…”
Section: Concept Of Multiphase Reliability Growthmentioning
confidence: 95%
See 3 more Smart Citations
“…This paper aims to extend the preliminary findings [22] to a multiphase reliability growth environment. The study is motivated to address the stochastic behavior of latent failures and further mitigate their impact on product reliability.…”
Section: Concept Of Multiphase Reliability Growthmentioning
confidence: 95%
“…Ellner and Hall [21] proposed an RGP model to estimate system reliability growth taking into account latent failures. Jin and Wang [22] formulated a multicriteria programming model to maximize field system reliability through optimal CA decisions. These studies show that GRP is an effective approach to drive the product reliability if extended in-house testing is infeasible in early design and prototyping phase.…”
Section: Concept Of Multiphase Reliability Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that the reliability growth rates for all components conform to the AMSAA model, the Coit model was presented which allocated the reliability growth testing time of components in series as a whole [20]. Jin and Wang provided three validity functions to express corrective actions and applied them to failure intensity models for projecting the mean time between failures (MTBF) of systems, a two-objective reliability growth model was provided for maximizing the reliability of the system and minimizing the uncertainty of reliability under limited corrective actions [21]. Calomeris and Herbert [22] pointed out that the experiment duration, primary MTBF, and goal MTBF all have a big influence on the growth pattern, but no further research has been found.…”
Section: Introductionmentioning
confidence: 99%